2021
DOI: 10.1017/jfm.2021.522
|View full text |Cite
|
Sign up to set email alerts
|

Exact coherent structures and shadowing in turbulent Taylor–Couette flow

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 72 publications
(87 reference statements)
3
30
0
Order By: Relevance
“…The stability analysis reflected in figure 3 reveals at least two more Hopf bifurcations of the already unstable DRW as is increased beyond the value for the onset of CH-DRW. Solution branches issued from these Hopf points and subsequent bifurcation cascades like the one we report may probably contribute, along with CH-DRW, through global bifurcations involving crises and mergers, to the formation of the strange set that sustains spatiotemporally chaotic dynamics at higher (Krygier, Pughe-Sanford & Grigoriev 2021).…”
Section: Structure and Stability Of Drw And Their Role In The Dynamicsmentioning
confidence: 81%
“…The stability analysis reflected in figure 3 reveals at least two more Hopf bifurcations of the already unstable DRW as is increased beyond the value for the onset of CH-DRW. Solution branches issued from these Hopf points and subsequent bifurcation cascades like the one we report may probably contribute, along with CH-DRW, through global bifurcations involving crises and mergers, to the formation of the strange set that sustains spatiotemporally chaotic dynamics at higher (Krygier, Pughe-Sanford & Grigoriev 2021).…”
Section: Structure and Stability Of Drw And Their Role In The Dynamicsmentioning
confidence: 81%
“…Moreover, utilizing SRDMD, we extended the Page & Kerswell (2020) DMD-based periodic orbit search method to relative periodic orbits and showed that a guess for a relative periodic orbit can be generated by SRDMD even when turbulence does not follow the relative periodic orbit for a full period, enabling relative periodic orbit searches that would not have been possible via recurrent flow analysis (Chandler & Kerswell 2013). In the light of recent evidence (Krygier, Pughe-Sanford & Grigoriev 2021; Yalnız, Hof & Budanur 2021; Crowley et al. 2022) that the approaches of turbulence to periodic solutions are often not for a full period, we think that SRDMD-based approaches can accelerate relative periodic orbit searches in future studies.…”
Section: Discussionmentioning
confidence: 91%
“…In his seminal paper, Taylor explored the Γ 1 limit in which boundary effects of the top and bottom end caps are negligible; in contrast, we investigate the small aspect ratio (Γ = 1) and medium gap (η = 0.71) parameter regime, in which the end effects play a substantial role in driving the fluid motion. Relevant prior studies for this geometry are summarized in [30].…”
Section: Experimental Systemmentioning
confidence: 99%
“…The presence of a continuous (rotational) symmetry in Taylor-Couette flow implies that the most common ECSs will be relative, e.g. traveling waves or RPOs [28,30,32]. RPOs are solutions satisfying…”
Section: Exact Coherent Structures In Tcfmentioning
confidence: 99%
See 1 more Smart Citation